A Comparative Study of Transpancreatic Sphincterotomy, Double Guidewire Technique, and Precut Sphincterotomy in Difficult Naive Biliary Cannulations in a Tertiary Care Center in Western India - Chopra, Shivani; Rawat, Vikramaditya; Ingle, Meghraj; Lad, Saiprasad; Sasikumar, Deepak; Borkar, Vinay D.; Lunagariya, Yatin; B., Kiran; Shah, Mit; Tailor, Chintan; Patil, Somraj (Journal of Digestive Endoscopy, 2024)
Introduction Difficult biliary cannulation leads to prolonged papillary manipulation and repeated attempts at cannulation are known to increase the risk of postendoscopic retrograde cholangiopancreatography (ERCP) pancreatitis. This study aims to compare the efficacy and complications of three rescue methods, transpancreatic biliary sphincterotomy (TP), double guidewire technique (DGW), and precut sphincterotomy (precut) in difficult common bile duct (CBD) cannulations.Methods Seventy-six patients (>12 years of age) with a native papilla undergoing ERCP for biliary cannulation were recruited. Those who had inadvertent pancreatic duct cannulations (>1) were included. A pancreatic stent was inserted in all cases. They underwent either DGW (n = 25), precut (n = 25), or TP (n = 26) as rescue methods and were compared in terms of the success of cannulation and post-ERCP complications.Results Of the total 76 cases, 82% were for benign indications, the most common being choledocholithiasis (69.7%). Jaundice was noted in 52% (n = 13/25), 60% (n = 15/25), and 38.5% (n = 10/26) of the DGW, precut, and TP cases, while 40% (n = 10/25), 12% (n = 3/25), and 30.8% (n = 8/26), respectively, were in cholangitis at presentation. The most common type of papilla was type 1 overall and each subgroup. While successful cannulation was achieved in 88.5% (n = 23/26) of TP and 84% (n = 21/25) of the DGW group, only 64% (n = 16/25) of the precut cases were cannulated. Three (n = 3/25) cases had mild bleeding and two mild pancreatitis, one severe pancreatitis, and one perforation were recorded in the precut group. One patient each had severe and mild pancreatitis in the DGW group, while one had mild pancreatitis and two had moderate pancreatitis in the TP group. All the patients were managed conservatively.Conclusion There was no significant difference in the technical success rate (p = 0.075) as well as complications (p = 0.117) between the three salvage methods for difficult naive CBD cannulations.
Keywords: difficult biliary cannulation; ERCP; double guidewire; precut; transpancreatic sphincterotomy